Financial Inclusion, Mobile Phone Diffusion, and Economic Growth; Evidence from Africa - Tough Chinoda; Joseph Olorunfemi Akande (International Journal of Economics and Financial Issues, 2019)
Whether finance enhances growth has continued to be a major debate among academics in the bids to drive economic growth and development. Hitherto, empirical studies focusing on Africa in addressing these issues for the expected regional sustainable growth are rare. This study applied structural equation modelling to simultaneously analyse mobile phones diffusion, financial inclusion, and economic growth in a panel of 32 African countries over the period from 2004 to 2016. The results provided evidence that financial inclusion affects economic growth via mobile phones. This study has implication for managing the deployment of mobile phones by for finance and growth relevance in Africa. Keywords: Financial inclusion, mobile phones diffusion, economic growth, structural equation modelling JEL Classifications: B26; C58; G21 DOI: https://doi.org/10.32479/ijefi.8256